Volleyball Skills-Oriented Physical Education Learning: A Literature Review - Hakim, Hikmad; Sahabuddin, Sahabuddin (Sains Global Institut, Indonesia, 2025)
This literature review examines recent research on volleyball skills-oriented physical education learning, focusing on methods, outcomes, and pedagogical innovations over the past decade. Analysis of 30 peer-reviewed studies from national and Scopus-indexed journals reveals that play-based learning methods consistently improve volleyball fundamental skills, particularly underhand passing, with skill acquisition gains ranging from 18% to 35% (Iqbal et al., 2025; Agustina et al., 2023). Movement coordination learning models contribute to enhanced motor control and game performance, reporting improvements in reaction time and accuracy by approximately 22% (Risma et al., 2024). Technological interventions such as e-books and visual imagery are validated as practical tools to increase skill proficiency and student engagement, showing up to 28% enhancement in learning outcomes (Endriani et al., 2022; Risma et al., 2024). Furthermore, pedagogical models including the Sport Education Model (SEM) and Teaching Games for Understanding (TGfU) positively impact both technical volleyball skills and socio-emotional learning, with noted increases in student motivation and life skills by 25% (Munar et al., 2025; Nascimento Junior et al., 2024). Feedback mechanisms and cooperative learning approaches also play critical roles in optimizing skill development and retention. However, research gaps remain in long-term effects and comparative efficacy across different age groups and skill levels. This review underscores the importance of diverse, student-centered teaching strategies supported by technology and feedback to enhance volleyball skills in physical education. Recommendations for future research emphasize longitudinal studies and the integration of physical literacy frameworks.